Combined MitraClip and Left Atrial Appendage Occlusion: Is It Still a Utopia? - Belli, Martina; Zanin, Federico; Macrini, Massimiliano; Barone, Lucy; Marchei, Massimo; Muscoli, Saverio; Prandi, Francesca Romana; Sergi, Domenico; Di Luozzo, Marco; Romeo, Francesco; Barillà, Francesco (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting 32 million individuals worldwide, particularly the elderly. It is the main cause of ischemic strokes. Oral anticoagulation (OAC) is the gold standard strategy for stroke prevention. Still, there is a not negligible share of patients who have contraindications to this therapy, more frequently due to an increased risk of bleeding. AF is often associated with moderate-severe mitral regurgitation (MR), the second most frequent valvular disease in elderly patients. Data from the literature reported that more than half of patients with severe mitral regurgitation are not suitable candidates for cardiac surgery. Given the progressive aging of the population and the simultaneous increase in the number of patients with comorbidities, the advent of new therapeutic strategies, such as the combined approach of Left Atrial Appendage Occlusion (LAAO) and MitraClip procedure, is acquiring great interest. At present, the category of patients who may benefit from combined percutaneous therapies and the long-term risks and benefits might not have been identified. Despite the efforts of researchers, the correct selection of patients is a very important clinical need that has not yet been met to avoid committing human and financial resources to interventions that may be unnecessary. It is conceivable that the most modern and recent innovations in cardiovascular imaging, particularly three-dimensional echocardiography and new methods of volume imaging, could improve our ability to select patients appropriately. Since data in the literature are scarce, future studies will be needed to evaluate the efficacy and safety of combined MitraClip and LAA occlusion.